Teaching Higher-Order Thinking Skills in Public Elementary Schools in Mexico - Heffington, Deon Victoria (2023)
The importance of developing Higher-Order Thinking Skills (HOTS) in the XXI century has become highly relevant around the world (Benjamin, 2008; Dwyer et al. 2014; Ku, 2009; Preus, 2012; Rosefsky-Saavedra y Opfer, 2012). The Organisation for Economic Co-operation and Development [OECD] (2018) highlights the importance of preparing students to become capable of performing in the global world. In Mexico, the educational standards also emphasize the importance of developing critical thinking skills and problem solving (Secretaría de Educación Pública [SEP] (2020). However, one of the main problems constitutes the ambiguity in the construct of HOTS (Cuban, 1984; Lewis y Smith, 1993; Newmann, 1987; 1990; Stanley, 1998). Moreover, it exists a lack of research on HOTS in Mexico (Díaz-Barriga, 2001), especially in terms of teacher and student perceptions, the activities used by teachers in classrooms to develop HOTS, and the factors that can influence the development of HOTS. Therefore, the main goal of this mixed methods study was to explore teacher perceptions regarding HOTS and the techniques used to develop HOTS in public elementary classrooms in southeastern Mexico through a sequential mixed design (Creswell & Clark, 2018). Moreover, the researchers analyzed the numerical data and nominal data by using a survey. While the quantitative analysis included descriptive statistics, the qualitative one was based on principles of the Constant Comparative Method (Merriam y Tisdell, 2016). In both cases, the software MAXQDA PRO, 15.0 was used for computations. In terms of the findings of the investigation, they provide insight into the perceptions of teachers regarding the definition of HOTS, techniques for teaching HOTS in public elementary schools, as well as how HOTS can be assessed.